1960
DOI: 10.1063/1.1730987
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Evidence for Triplet State Quenching by Paramagnetic Species

Abstract: LETTERS TO THE EDITOR effects. Our results are in fair agreement with those obtained by electron diffraction; the 0-0 bond distance provides the most reliable comparison between the two methods and agrees within the experimental errors.This work was suggested by Professor E. B. Wilson, Jr., and the major portion of it was done in his laboratory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1962
1962
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Soc., 52, 3139 (1930). " The initial benzophenone concentration in all of the experiments was 0.10 M. 6 The solvent used for all experiments listed here was benzene unless indicated otherwise. 0 DPM is dipivaloylmethanate; AA is acetylacetonate; MAA is 3-methylacetylacetonate; AC is 2-acetylcyclohexanonate.…”
Section: Hb-bhmentioning
confidence: 99%
“…Soc., 52, 3139 (1930). " The initial benzophenone concentration in all of the experiments was 0.10 M. 6 The solvent used for all experiments listed here was benzene unless indicated otherwise. 0 DPM is dipivaloylmethanate; AA is acetylacetonate; MAA is 3-methylacetylacetonate; AC is 2-acetylcyclohexanonate.…”
Section: Hb-bhmentioning
confidence: 99%
“…With 0.1 wt.% of well-dispersed quenchers, an efficient quenching effect can be achieved even in 5 nm separated stabilizer and chromophore [29] . The earlier studies on the quenching effects upon photo-oxidation have been conducted by researchers and it was reported that the most common quenchers are the metal chelates [54] . Metal chelates that are derived from b-diketone give potential reactivity in photo-reduction of benzophenone (C 12 H 10 CO) by benzhydrol (C 12 H 10 CHOH) [55] .…”
Section: Roles Of Metals and Metallic Compounds As Degradation Retardersmentioning
confidence: 99%
“…134-135°; ultraviolet spectrum: Xmax 333, 460, 490, and 522 µ; n.m.r. spectrum: C-2, C-3, and C-6 methoxyl, 4.04, 4.08, 4.16; C-7 hydroxyl, 6.90 (broad); C-5 and C-8 hydroxyl, 12.16 and 13.30. Methylation of 9 with diazomethane yielded 2,3,6,7tetramethoxynaphthazarin, m.p. 185-186°( lit.8 m.p.…”
mentioning
confidence: 99%